Islet cells contribute to pncreatic carcinogenesis in an animal model - Ghamari, Mohamed el-; Bergmann, Frank; Schmied, Bruno; Weitz, Jürgen; Ulrich, Alexis (Pancreas, 2011)
Objectives: - In the hamster model, pancreatic ductal adenocarcinoma develops after treatment with N-nitrosobis-(2-oxopropyl)amin (BOP). In this model, Langerhans islets play a central role in carcinogenesis. In contrast, treatment with BOP in rats and mice did not result in cancer development. We investigated whether pancreatic tumors develop after orthotopic implantation of hamster islets into severe combined immunodeficiency mouse pancreases and subsequent treatment with BOP. This occurrence would suggest that pancreatrophic carcinogens are metabolized by islet cells. - Methods: - Twenty-four severe combined immunodeficiency mice were separated into 2 groups of 12 animals. Five hundred hamster islets were implanted in the splenic lobe of the mouse pancreases in the treatment group, whereas animals of the control group received a sham operation. All animals were treated with BOP for 5 weeks. One year later, the animals were killed and investigated for tumors. - Results: - Carcinomas developed in 3 animals in the treatment group and none in the control group. The tumors displayed the histomorphological phenotype pancreatic ductal adenocarcinoma. - Conclusions: - Islet cells seem to play a role in pancreatic carcinogenesis in this animal model and therefore represent useful targets for future investigations on the putative role of islet cells during pancreatic ductal adenocarcinoma tumorigenesis.
Gesehen am 12.04.2022